2003
DOI: 10.1590/s0101-20612003000400004
|View full text |Cite
|
Sign up to set email alerts
|

Influência do teor de nitrogênio no cultivo de Spirulina maxima em duas temperaturas - Parte I: Alteração da composição da biomassa

Abstract: Influência do teor de nitrogênio na alteração da composição da biomassa Spirulina maxima, Santos et al. -INTRODUÇÃOSpirulina maxima é uma cianobactéria que pode ser utilizada na composição de alimentos dietéticos e tem sido objeto de estudos em vários países como Israel, Japão, França, E.U.A. e Brasil [2,3]. Juntamente com outras microalgas, podem ser utilizadas como fonte alternativa de proteínas, lipídios (ácidos graxos essenciais), ficocianina e outros, em alimentos e rações. Desenvolve-se bem na faixa de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…In another study done by Santos et al (2003), it was observed that lipid contents decrease in Spirulina maxima microalgae from 23.16 to 8.35% with a drastic increase in nitrogen concentration from zero to 2.5gL -1 . However, there was a lower variation in lipid content when the nitrogen concentration remained between zero and 0.2gL -1 .…”
Section: Discussionmentioning
confidence: 91%
“…In another study done by Santos et al (2003), it was observed that lipid contents decrease in Spirulina maxima microalgae from 23.16 to 8.35% with a drastic increase in nitrogen concentration from zero to 2.5gL -1 . However, there was a lower variation in lipid content when the nitrogen concentration remained between zero and 0.2gL -1 .…”
Section: Discussionmentioning
confidence: 91%
“…They found that nitrate deficiency could cause the protein content and the chlorophyll level to decrease while carbohydrate and lipids would exhibit a species-specific change. Santos et al 154 have shown that the lipid content in Spirulina increased by approximately three times with the decrease of both nitrogen concentration and temperature. Improvement of solar conversion efficiency is of critical importance for the development of algae-to-biofuel technologies.…”
Section: Manipulation Of Microalgal Metabolismmentioning
confidence: 98%
“…A muitos fatores que pode influenciar o crescimento do gênero Arthrospyra (Spirulina), entre eles a fonte de nitrogênio. A falta de nitrogênio pode afetar o crescimento, sendo assim influencia a composição de lipídeos e "leva um decréscimo na produção de ficocianina e clorofila, " e consequente perda de suas características de cor verde azulado (SANTOS; MACEDO;ALEGRE, 2003).…”
Section: Introductionunclassified